Cost‐Effectiveness of Computer‐Assisted Cytology in a Primary hrHPV‐Based Cervical Cancer Screening Programme - Ellen M. G. Olthof; S. Kaljouw; Folkert J. vanKemenade; Anne M. Uyterlinde; Inge M. C. M. deKok (Cancer Medicine)
ABSTRACT Background Computer‐assisted screening (CAS) shows equal performance compared to manual screening, although results are heterogeneous. Furthermore, using CAS may save costs through a potentially increased screening productivity of technicians, therefore also offering a solution for temporary and structural capacity shortage. We evaluated the circumstances under which CAS will be cost‐effective compared to manual cytology triage in a primary HPV‐based cervical screening programme. Methods Microsimulation model MISCAN‐Cervix was used to evaluate 198 different CAS scenarios with varying probabilities to detect cervical intraepithelial neoplasia grade 1 (CIN1) and CIN3 and cost reductions per test, compared to manual cytology triage. Cost‐effectiveness was evaluated by costs per (quality‐adjusted) life year ((QA)LY) gained. Results CAS will be cost‐effective in all scenarios, except for the following combinations: (1) no cost reduction and an increased probability of detecting CIN1, (2) a cost reduction of €2 per test and an increased probability of detecting CIN1 from 4% onwards or (3) a cost reduction of €4 per test and an increased probability of detecting CIN1 from 6% onwards, compared to manual cytology triage. All CAS scenarios with any reduction in the probability of detecting CIN1 (i.e., increased CIN2+ specificity), or a reduction in costs from €6 per test onwards suggested a more cost‐effective strategy compared to manual cytology triage. Conclusion As we based our analysis on a realistic range in costs and test performance, the implementation of CAS is likely to be cost‐effective. Our results can be used as a guideline to advise when to choose CAS instead of manual cytology triage.